Penerapan pembelajaran model STAD (Student Team Achievement Division) untuk Meningkatkan Prestasi Belajar Matematika Siswa di SDN 39 Cakranegara - Lazarus, Joni (UNDIKMA, 2020)
This study aims to improve students' mathematics learning achievement through the application of STAD model learning. This research method uses a classroom action research method with research subjects namely fifth grade students of SD Negeri 39 Cakranegara. The research instrument used observation and tests. The data analysis technique used in this research was qualitative and quantitative descriptive analysis. The results of this study indicate that the application of the STAD (Student Team Achievement Division) model of learning in building materials in class V SDN 39 Cakranegara is proven to improve student learning outcomes, this can be seen from the acquisition of class average scores from student test results at each stage The cycle is increasing, namely, the class average value in pre-cycle is 50, in cycle I is 60.70 and in cycle II is 75.35.